Particular issues of the conformity of the USC-2000 coordinate system to the land legislation - Avramchuk, B.; Patiyuk, O. (Land Management, Cadastre and Land Monitoring, 2019)
The coordinate basis for the implementation of land management works is the State Geodetic Reference System of the USC-2000 coordinates. However, as practice of land management shows, public information from the State Land Cadastre is reflected in the coordinate system of 1963 (SC-63).In this case, in most cases, the recalculation of areas between the above-mentioned coordinate systems leads to a change in the area of land .Therefore, it is important to highlight some issues regarding the use of the USC-2000 coordinate system with the current land laws that may arise when used in conjunction with the SC-63, namely the possible excess of the rules for free remittance. land plots to citizens in the transition to a single state coordinate system.To investigate such distortions, the authors designed three model land plots in the coordinate system SC-63 in the maximum allowable area in accordance with the norms of free transfer for the maintenance of personal from the eagle economy (2,0000   ha) for the construction and maintenance of a residential building, commercial buildings and structures (private plot) in villages (0,2500 hectares) and for gardening respectively (0,1200 hectares).Subsequently, using the standard features of the licensed Digitals software , the coordinates of each plot of land from the SC-63 system in the USC-2000 were recalculated within the three selected administrative units .For the purpose of visual representation, the coordinates of the first point of the listed land plots in USC-2000 were given the coordinates of the first point of land in the system SC-63 .Changes or distortions in squares, lines or angles are obvious when moving from one coordinate system to another if they are based on ellipsoid referents with different parameters.However, it should be noted that the compliance of the USC-2000 with the land legislation, and in particular the excess of the area of established norms for the free transfer of land plots to citizens in modern conditions in the transition to a legally established single frame of reference USC-2000, requires further consideration and resolution, for example, by clarification legislation .Keywords: Land Code, norms of free privatization, reference system of coordinates, SC-63, USC-2000.